دراسة تأثير بعض العوامل على نمو الطحلب الأخضر Scendesmus acutus مخبرياً - حمود, نديم; ميهوب, حامد; علان, طارق (Latakia University Journal -Biological Sciences Series, 2016)
تم في هذا البحث اختبار تأثير تراكيز مختلفة من الفوسفات والنترات ومستخلص التربة على نمو عزلة من طحلبScendesmus acutus المعزول من بعض المسطحات المائية المحلية ، تم حساب عدد الخلايا ومعدل النمو وزمن التضاعف لجميع المزارع الطحلبية ولمدة 30 يوم.بلغ أعلى معدل نمو 3.90 عند استخدام مزيج من المحاليل الثلاثة بتراكيز(1 غ/ل نترات + 0.05 غ/ل فوسفات + 10مل/100 محلول تربة)، حيث وصل عدد الخلايا إلى 8861.11 خلية /مل وذلك في اليوم 24 من الزراعة، وبأقل زمن تضاعف 1.85، في حين كان أعلى معدل نمو عند استخدام محلول التربة بمفرده 2.86 وأقل زمن تضاعف 2.13 وذلك عند تركيز 16مل/100مل، في حين انخفض معدل النمو وزاد زمن التضاعف عند استخدام محلول النترات والفوسفات كلاً بمفرده، حيث بلغ أعلى معدل نمو 2.13 و1.76 وأقل زمن تضاعف 3.39 و4.11على الترتيب.The effect of different concentrations of phosphate and nitrate and soil extracted on the isolated growth isolation of Scendesmus acutus which is isolated from some local aquatic areas has tested in this research, the number of cells and growth range and duplicated time of all algal cultures among thirty five days has counted.The highest growth range was 3.90 by using a mixture of the three solutions in concentrations (1g/l nitrate + 0.05g/l phosphate + 10 ml / 100 of soil solution), the numbers of cells reached to 8861.11 in the twenty fourth day of culture, and in the lowest duplicated time 10.85, whereas the highest growth range was by using soil solution alone 2.86 and the lowest duplicated time 2.13 at concentration 16/100ml, whereas the growth range decreased and duplicated time increased by using nitrate and phosphate solution all by its own, while the highest growth range reached to 2.13 and 1.76 and lowest duplicated time 3.39 and 4.11 in order